Detrital carbonate sedimentation of the Rocas Atoll, South Atlantic - NATAN S. PEREIRA (Anais da Academia Brasileira de Ciências, 2013)
Located 266 km offshore Brazilian coast, Rocas Reef complex is the only atoll in the South Atlantic. Two scientific expeditions carried out detailed sedimentological studies of the complex. Sand texture was dominant in the sedimentary environment, although other textures such as gravel, sandy gravel and gravelly sand, were also observed. Mean size ranged from fine sand to coarse sand (-1.23 to 2.34ø), with an average value of 0.69ø (sand fraction), which from a geological perspective represents a high-energy environment. The values of mean size varied in the different geomorphologic compartments, a response to variable hydrodynamics on the reef. Sorting ranged from very well sorted to poorly sorted, with a mean value of 0.97ø (moderately sorted). The values of mean size and sorting are directly proportional (i.e. the larger the grain size, the better the sorting), a fact that might be controlled by the decreasing of organism diversity that contributes to the sedimentary environment as the mean size of the particles increase. Skewness parameter was used to correlate positive values to depositional environments. The Kurtosis parameter showed little relevance in this study. The sedimentary particles analyzed are exclusively composed of biogenic grains. In total eleven major groups were described, coralline algae being the most unusual.